2013
DOI: 10.1007/s13762-013-0215-2
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of tetracycline from montmorillonite by aluminum, calcium, and sodium: an indication of intercalation stability

Abstract: As the uptake of cationic drugs, such as tetracycline (TC), was attributed to cation exchange, the stability of adsorbed TC on a Ca-montmorillonite SAz-2 was studied using cationic solutions of different valence charges under different pH conditions. At the initial loading of 356 mg g -1 , the amounts of TC desorbed by 0.05 M AlCl 3 , CaCl 2 , and NaCl were 133 ± 4, 83 ± 6, and 50 ± 4 mg g -1 , respectively, or 37, 23, and 14 %. However, when the amount or percentage of TC desorbed was normalized to the equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Similar to many previous studies (Myers et al, 1983;Kulshrestha et al, 2004;Chang et al, 2014), the FTIR spectra of TC in Fig. 9 indicate that the band positions of several characteristic peaks in the recorded region changed once TC was adsorbed onto Fe-Mt, while no change occurred for the band centered at 1456 cm −1 , which can be ascribed to the C_C skeleton in ring-A.…”
Section: Adsorption Mechanismssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to many previous studies (Myers et al, 1983;Kulshrestha et al, 2004;Chang et al, 2014), the FTIR spectra of TC in Fig. 9 indicate that the band positions of several characteristic peaks in the recorded region changed once TC was adsorbed onto Fe-Mt, while no change occurred for the band centered at 1456 cm −1 , which can be ascribed to the C_C skeleton in ring-A.…”
Section: Adsorption Mechanismssupporting
confidence: 87%
“…Thus, it is deduced that most of the TC adsorption occurs outside the Mt counterpart particles in FeMt, with which certain surface complexes of TC are thus formed. Chang et al (2014) reported that the XRD patterns of Ca 2+ -Mt revealed no change in the basal spacings before and after TC desorption by using Al 3+ , Ca 2+ and Na + cations, suggesting that the TC retention is largely distributed on the external surfaces. This is mainly because both the -CONH 2 group in TC 1 and -OH group in TC 2 can directly bind to those negative surface sites via a 'cation-bridging' interaction (MacKay and Canterbury, 2005).…”
Section: Adsorption Mechanismsmentioning
confidence: 98%
“…The band at 1614 cm −1 shifted to a higher frequency, indicating that the carbonyl groups or the amid-NH in ring A may have been influenced by the complexation of TCs and Fe (III) on the sorbent. This was consistent with the complexation of TC and hydrous oxides of Al, Fe [2,31]. The intensity of the 1581 cm −1 band decreased, and the slight shift of the 1455 cm −1 band indicated that carbonyl groups of ring C or amid-NH in ring A of the TCs may form complexes with Fe (III) on the sorbent.…”
Section: Adsorption Mechanismsupporting
confidence: 80%
“…5a) followed the study of Gu et al and Chang et al [2,31]. The 1672 and 1523 cm −1 bands were assigned to the carbonyl and amino groups of the amide in ring A, respectively.…”
Section: Adsorption Mechanismmentioning
confidence: 94%
“…As such, a series of adsorbents including natural and synthetic materials such as montmorillonite , carbon nanotubes , Fe‐OMC‐100 , Fe‐Mn binary oxide , and MnFe 2 O 4 /activated carbon magnetic composites have been employed for the removal of tetracycline from water. Among these adsorbents, the biosorbents are believed to be promising on the basis of their low cost, high adsorption efficiency and wide availabilities .…”
Section: Introductionmentioning
confidence: 99%